2018
DOI: 10.2807/1560-7917.es.2018.23.9.17-00384
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Coxiella burnetii antibodies and chronic Q fever among post-mortal and living donors of tissues and cells from 2010 to 2015 in the Netherlands

Abstract: BackgroundAfter a large Q fever outbreak in the Netherlands in the period from 2007 to 2010, the risk of Q fever transmission through tissue and cell transplantation from undiagnosed chronic Q fever cases became a potential issue. Aim: We aimed to evaluate the risk of Q fever transmission through tissue and cell transplantation. Methods: We performed a retrospective observational cohort study among 15,133 Dutch donors of tissues and stem cells from 2010 to 2015 to assess seroprevalence of Coxiella burnetii ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
1
4
1
Order By: Relevance
“…Lower prevalence compared to the present study has been observed in the Netherlands in a 2006-2007 study based on random samples from the general population (2.4%) [4] and in a 2010-2015 study based on tissue and cell donor samples (2%) [59]. In contrast, in the early study from 1983, higher prevalence was observed representing the general adult population (15.2%-60.4%) [60].…”
Section: Prevalencecontrasting
confidence: 81%
“…Lower prevalence compared to the present study has been observed in the Netherlands in a 2006-2007 study based on random samples from the general population (2.4%) [4] and in a 2010-2015 study based on tissue and cell donor samples (2%) [59]. In contrast, in the early study from 1983, higher prevalence was observed representing the general adult population (15.2%-60.4%) [60].…”
Section: Prevalencecontrasting
confidence: 81%
“…The results that we have obtained serve to confirm the effectiveness of using DBS samples for the serological detection of antibodies, whilst extending the applicability of current commercial immunoassays for the detection of SARS-CoV-2. Our results are in accordance with the expected seroprevalence of Coxiella burnetii and parvovirus in Europe [11][12][13] . Of importance is that we were able to detect both IgG and IgA antibodies in the patient with a history of SARS-CoV-2 infection using the commercially available kits.…”
Section: Discussionsupporting
confidence: 91%
“…ELISA assay DBS eluates were subjected to the following commercial immunoassay kits: Parvovirus B19 IgG (Kit number ESR122G, Serion Diagnostic, Germany), Coxiella burnetii Phase 2 IgG (Kit number ESR1312G, Serion Diagnostics), Anti-SARS-CoV-2-ELISA IgG and Anti-SARS-CoV-2-ELISA IgA (Kit numbers EI 2606-9601 G and EI 2606-9601 A, Euroimmun, Lübeck, Germany) and the EDI™ Novel Coronavirus COVID-19 IgG ELISA kit (Kit number KT-1032, Epitope Diagnostics, San Diego, USA) to detect the presence of antibodies. Because seroprevalence is high for parvovirus 11 and low for Coxiella burnetii in Europe 12,13 , the parvovirus B19 IgG and Coxiella burnetti Phase 2 IgG ELISAs acted as positive and negative controls, respectively. All the listed commercial immunoassays in our study require a minimum of 10 µl serum sample to be diluted in a 1:100 dilution ratio with sample diluent at a final volume of 1000 µl.…”
Section: Dbs Samplingmentioning
confidence: 99%
“…The median infectious dose (ID50) was estimated at 1.5 bacteria and indicates the high infectivity of C. burnetii via aerosols [ 9 ]. In the Netherlands, drifting particulate matter from C. burnetii positive dairy goat farms led to the world’s largest Q fever epidemic, with more than 4000 reported human cases and an estimated number of about 40,000 infected individuals [ 10 , 11 ]. Furthermore, one ‘super-spreading’ ewe infected 299 visitors at a German farmers’ market [ 12 ].…”
Section: Introductionmentioning
confidence: 99%